Bibliometric analysis: Spatial skills and gender in education - Raditya, Aji; Syazali, Muhamad (Desimal: Jurnal Matematika, 2024)
Spatial skills, the ability to perceive, understand, and manipulate shapes and spatial relationships, are fundamental to human cognition and have a significant impact on success in STEM (Science, Technology, Engineering, and Mathematics) career. The purpose of this study is to analyze the scientific research related to spatial skills and gender in education on Scopus database. This research also reveals the current research trends and research gaps on this subject. Bibliometric analysis is used to answer those objectives, with platforms such as R packages (Bibliometrix) and Vos Viewer software to help the analysis. This study addresses four research issues as follows: (i) the landscape of research on spatial skills and gender; (ii) the leading countries and institutions on spatial skills and gender research; (iii) the most cited journal; and (iv) the most cited authors; (v) the most cited articles; (vi) the most popular and least popular keywords.